Natural fiber composite manufacture using wrapped hemp roving with PA12. (2020) - Corbin, Anne-Clémence; Ferreira, Manuela; Labanieh, Ahmad Rashed; Soulat, Damien
Abstract: The objective of this study is to develop hybrid hemp/thermoplastic roving adapted for composite manufacture. The hybrid roving has to be enough resistant to sustain the tension and abrasion stresses caused by the textile production processes. For this purpose, a multifilament of polyamide 12 is wrapped around a hemp roving. This wrapped roving is used to manufacture a woven preform then the composite plate is produced by thermocompression process. The textile properties and mechanical properties are characterized at each product scale roving, preform and composite. Microscopic observations are also made to evaluate the impregnation quality of the hemp composite.